Postfire dynamics of standing dead tree stock in northern boreal forests - Mukhortova Liudmila; Krivobokov Leonid; Schepaschenko Dmitry (BIO Web of Conferences, 2022)
Wildfire is one of the main forest disturbing factors in the boreal zone of Siberia that can cause significant changes in tree stands dynamics. Tree mortality caused by fire can significantly increase a standing dead tree pool that is one of the poorly studied components of forest ecosystems. The aim of this study was assessing of post-fire changes in the standing dead tree pool in northern boreal larch forests of Central Siberia (Russia). We analyzed dynamics of the standing dead tree stock on experimental plots, which were affected by wildfire of moderate severity in 2013. The stock of standing dead trees was measured on these plots before and 1, 2, and 7 years after the fire. It was found that about half of the pre-fire standing dead trees fall down during the first year after the fire. At the same time, tree mortality caused by the fire significantly contributed to the total standing dead tree stock in these ecosystems. Our study showed that a significant part of the pre-fire standing dead trees and trees killed by fire can remain standing after the moderate severity fire. This standing dead wood conserves carbon for a long time.